Long internal direct repeat in Epstein-Barr virus DNA. - Cheung, A (1982)
The nucleotide sequence of the long internal reiteration. IR1, of Epstein-Barr Virus DNA has been determined. The repeat unit is 3,071 base pairs which are 66.8% guanine plus cytosine. There is a CCAAT sequence 39 nucleotides 5' to a TATAA, which could indicate a promotor for transcription. The longest open reading frame is 1,124 base pairs. Also within IR1 is a sequence homologous to the papovavirus origin of DNA replication. The ori-like sequence is within a long palindromic region which is 500 base pairs overall. The palidromic region shares common features with the Alu family members and with eucaryotic transposable elements. The juncture between the short unique region (U1) and IR1 is also sequenced. The transition occurs in BamHI-C at 1,214 base pairs before the BamHI site in the first repeat of IR1. The transition from IR1 to the rightward unique region (U2) has been reported to be at 636 base pairs after the BamHI site in the last repeat of IR1. Thus, relative to the start of IR1 at the juncture with U1, the last copy of IR1 is a partial repeat which contains only the beginning 1,850 base pairs.